Development of New Formula Microcapsules from Nutmeg Essential Oil Using Sucrose Esters and Magnesium Aluminometasilicate - Inga Matulyte; Giedre Kasparaviciene; Jurga Bernatoniene (Pharmaceutics, 2020)
Essential oils are volatile liquids which evaporate and lose their pharmacological effect when exposed to the environment. The aim of this study is to protect nutmeg essential oil from environmental factors by encapsulation (shell material, sodium alginate) and determine the influence of crosslinker concentration (2%, 5% calcium chloride), different emulsifiers (polysorbate 80, sucrose esters), and magnesium aluminometasilicate on microcapsule physical parameters, encapsulation efficiency (EE), swelling index (SI), and other parameters. Nutmeg essential oil (NEO)-loaded calcium alginate microcapsules were prepared by extrusion. The swelling test was performed with and without enzymes in simulated gastric, intestinal, and gastrointestinal media. This study shows that the crosslinker concentration has a significant influence on EE, with 2% calcium chloride solution being more effective than 5%, and capsules being softer with 2% crosslinker solution. Using sucrose esters, EE is higher when polysorbate 80 is used. The swelling index is nearly three times higher in an intestinal medium without enzymes than in the medium with pancreatin. Microcapsule physical parameters depend on the excipients: the hardest capsules were obtained with the biggest amount of sodium alginate; the largest with magnesium aluminometasilicate. Sucrose esters and magnesium aluminometasilicate are new materials used in extrusion.